The Rational Expectations Hypothesis: An assessment on its real world application (2014)
The Rational Expectations Hypothesis was first developed as a theoretical technique aimed at explaining agents’ behavior in a given environment -- In particular, it describes how the outcome of a given economic phenomenon depends to a certain degree on what agents expect to happen -- Subsequently, it was introduced into macroeconomic models as a way to explain the ineffectiveness of monetary policy -- Since then, most of these models have been based on the rational expectations assumption -- This paper assesses the real life application of this feature based on two arguments: the determination of an objective reality through beliefs and subjective expectations; and the exclusion of the evolution of human knowledge and innovation in macroeconomic models